THE ROLE OF FORMATIVE ASSESSMENT IN DEVELOPING - Toshboyeva Sevinch Sultonmurod qizi (International Journal of Literature and Language Studies, 2026)
The increasing demand for effective English communication has made communicative competence one of the primary objectives of modern language education. Formative assessment plays a crucial role in supporting this objective by providing continuous feedback, monitoring learners' progress, and improving teaching and learning processes. Unlike summative assessment, formative assessment focuses on learning improvement rather than final achievement. This article examines the contribution of formative assessment to developing English communicative competence and highlights its benefits, challenges, and practical implications for English language teaching.